All of the Above: Lobbying Allied, Undecided, and Opposing Lawmakers in Committee and on the Floor. (June 2023) - Newmark, Adam; Nownes, Anthony J.
This paper asks: When seeking to influence legislation in Congress, do organized interests target legislative allies, opponents, undecideds, or some combination of these? We address this question with data from a survey of 836 Washington lobbyists. Our findings point to several conclusions, including the following: (1) Organized interests almost always lobby their legislative allies, whether they support or oppose legislation, and whether the legislation is at the committee or floor stage; (2) Organized interests seldom lobby only their allies, very often targeting opponents and undecideds; (3) Organized interests lobby legislative opponents when their group opponents are relatively powerful; (4) Organized interests lobby legislative opponents and undecideds more in conflictual policy environments than they do in non-conflictual policy environments; (5) Resource competition from other groups causes organized interests to shy away from lobbying non-allied lawmakers; and (6) Coalition joining is associated with less allies-only lobbying.